Manajemen Inovasi dan Kewirausahaan untuk Remaja di SMA Muhammadiyah 4 Sidayu Gresik - Wati, Hernum Daya (JURNAL PENGABDIAN MANAJEMEN, 2025)
The community service activity held at SMA Muhammadiyah 4 Sidayu Gresik aims to understand the level of understanding of high school students of the basic concepts of innovation and entrepreneurship, as well as explore the factors that influence their interest and participation in entrepreneurial activities. The method used in this service is to use a qualitative approach to explore the views, experiences, and obstacles faced by students in encouraging innovation and entrepreneurship. This research shows that teenagers at the high school level have a high interest in entrepreneurship, but still have a limited understanding of innovation management. Although most students are familiar with the concept of entrepreneurship, the application of innovation in entrepreneurial practice is still not optimal due to limited knowledge, experience, and mentoring.